Comparison of adult shift and non-shift workers’ physical activity and sleep behaviours: cross-sectional analysis from the Household Income and Labour Dynamics of Australia (HILDA) cohort - Fenwick, MJ; Oftedal, S; Kolbe-Alexander, TL; Duncan, MJ (My University, 2022)
Aim This study compares the pattern of physical activity and sleep between shift and non-shift workers using a novel physical activity–sleep index. By drawing from a diverse occupational population, this research aims to reduce any occupational specific biases which are prevalent in shift-work research. Subject and methods Current data included 7607 workers (shift workers n = 832) from the Household Income and Labour Dynamics of Australia cohort study. The combined physical activity–sleep index comprised three physical activity components and three sleep health components: achieving moderate (1pt) or high (2pts) IPAQ classification; accruing ≥30% of physical activity as vigorous intensity (1pt); meeting sleep duration recommendations on a work night (1pt); and non-work night (1pt); and reporting no insomnia symptoms (1pt) (higher score = healthy behaviour, max. 6). Generalised linear modelling was used to compare behaviours of shift and non-shift workers. Results Findings showed shift workers reported significantly lower activity–sleep scores (3.59 vs 3.73, p < 0.001), lower sleep behaviour sub-score (2.01 vs. 2.22, p < 0.001) and were more likely to report insomnia symptoms (p < 0.001) compared to non-shift workers. No difference was reported for overall physical activity (shift = 1.58 vs. non-shift = 1.51, p = 0.383).Conclusion When viewed in conjunction using the combined activity–sleep index, shift workers displayed significantly poorer combined behaviours when compared to non-shift workers.
Journal of Public Health
Keywords: Health and wellbeing; Income, wealth and finances; Labour market; Lifestyle